Real-time intravascular photoacoustic-ultrasound imaging of lipid-laden plaque in human coronary artery at 16 frames per second - Jie Hui (Nature Portfolio, 2017)
Abstract Intravascular photoacoustic-ultrasound (IVPA-US) imaging is an emerging hybrid modality for the detection of lipid-laden plaques, as it provides simultaneous morphological and lipid-specific chemical information of an artery wall. Real-time imaging and display at video-rate speed are critical for clinical utility of the IVPA-US imaging technology. Here, we demonstrate a portable IVPA-US system capable of imaging at up to 25 frames per second in real-time display mode. This unprecedented imaging speed was achieved by concurrent innovations in excitation laser source, rotary joint assembly, 1 mm IVPA-US catheter size, differentiated A-line strategy, and real-time image processing and display algorithms. Spatial resolution, chemical specificity, and capability for imaging highly dynamic objects were evaluated by phantoms to characterize system performance. An imaging speed of 16 frames per second was determined to be adequate to suppress motion artifacts from cardiac pulsation for in vivo applications. The translational capability of this system for the detection of lipid-laden plaques was validated by ex vivo imaging of an atherosclerotic human coronary artery at 16 frames per second, which showed strong correlation to gold-standard histopathology. Thus, this high-speed IVPA-US imaging system presents significant advances in the translational intravascular and other endoscopic applications.